The genome sequence of Bocage’s wall lizard, Podarcis bocagei (Lopez-Seoane, 1885) [version 1; peer review: 2 approved] - Joana Meier; Nathalie Feiner; Miguel A. Carretero; Tobias Uller (Wellcome Open Research)
We present a genome assembly from a female specimen of Podarcis bocagei (Bocage's wall lizard; Chordata; Lepidosauria; Squamata; Lacertidae). The assembly contains two haplotypes with total lengths of 1,615.19 megabases and 1,473.58 megabases. Most of the haplotype 1 assembly (97.72%) is scaffolded into 20 chromosomal pseudomolecules, including the W and Z sex chromosomes. Most of haplotype 2 (97.4%) is scaffolded into 18 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 17.4 kilobases.